Coronavirus disease 2019 (COVID-19): Immunological approaches and emerging pharmacologic treatments (2020)
The SARS-CoV-2 virus is an etiological agent of pandemic COVID-19, which spreads rapidly worldwide. No proven effective therapies currently exist for this virus, and efforts to develop antiviral strategies for the treatment of COVID-19 are underway. The rapidly increasing understanding of SARS-CoV-2 virology provides a notable number of possible immunological procedures and drug targets. However, gaps remain in our understanding of the pathogenesis of COVID-19. In this review, we describe the latest information in the context of immunological approaches and emerging current antiviral strategies for COVID-19 treatment.